2011
DOI: 10.1142/s0192415x11008610
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Polysaccharides: Immunomodulation and Potential Anti-Tumor Activities

Abstract: Ganoderma lucidum (G. lucidum), a basidiomycete white rot fungus, has long been prescribed to prevent and treat various human diseases, particularly in China, Japan, and Korea. Several classes of bioactive substances have been isolated and identified from G. lucidum, such as triterpenoids, polysaccharides, nucleosides, sterols, and alkaloids, among others. This paper examines the potential role of G. lucidum polysaccharide (GLPS) in tumor therapy and the possible mechanisms involved. Both in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
167
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(180 citation statements)
references
References 40 publications
3
167
0
7
Order By: Relevance
“…The structure and pharmacological effect(s) of polysaccharides produced by G. lucidum is being actively studied (13,20,21). The potential role of G. lucidum polysaccharide in tumor therapy and the possible mechanisms involved were examined (22). Both in vitro and in vivo studies suggested that the antitumor activities of the polysaccharides of G. lucidum are mediated by its immunomodulatory, antiangiogenic, and cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and pharmacological effect(s) of polysaccharides produced by G. lucidum is being actively studied (13,20,21). The potential role of G. lucidum polysaccharide in tumor therapy and the possible mechanisms involved were examined (22). Both in vitro and in vivo studies suggested that the antitumor activities of the polysaccharides of G. lucidum are mediated by its immunomodulatory, antiangiogenic, and cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies of Xu et al [21] suggested that anti-tumor activities of Ganoderma lucidum polysaccharides are mediated by their immunomodulatory, anti-angiogenic, and cytotoxic effects. Ganoderma lucidum polysaccharides affect immune cells and immune-related cells including B lymphocytes, T lymphocytes, dendritic cells, macrophages, and natural killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays G. lucidum has been used to treat and prevent cancer, immunological disorders, hepatitis, hypertension, and other diseases. Many studies have revealed that G. lucidum extracts can inhibit the growth of many tumor cells such as lung cancer cell, colorectal prostate cancer cells, and breast cancer cells (Li et al 2007;Liu and Zhang 2007;Xu et al 2011). The fruiting body of G. lucidum is made of polysaccharides, terpenoids, amino acids, alkaloids, and proteins, etc.…”
Section: Introductionmentioning
confidence: 99%